Pengaruh Penggunaan Metode ‘Ali Terhadap Kemampuan Tahsin dan Tahfidz Santriwati di Rumah Tahfidz Fatimah Yayasan Daarul Iman Kota Bengkulu - Pela Parma; Suryani Suryani; Desy Eka Citra Dewi (UIN Fatmawati Sukarno Bengkulu, 2024)
The purpose of this research was to determine the impact of using the 'Ali method on the tahsin and tahfidz (memorization) abilities of female students at the Tahfidz Fatimah House of the Daarul Iman Foundation in Bengkulu City. The study also aimed to explore the application of the 'Ali method of learning at the Tahfidz Fatimah House. This research utilized an experimental study with mixed methods and a One-Group concurrent embedded design. The research involved 67 students as the research population and 17 students as the research sample. For quantitative methods, data collection techniques included observation, documentation, and oral tests (pretest and post-test). For qualitative methods, observation, interviews, and documentation were used for data collection. The findings indicated that the 'Ali method had an impact on the tahsin and tahfidz abilities of the students at Rumah Tahfidz Fatimah, Daarul Iman Foundation, Bengkulu City. The Wilcoxon Match Pairs Test confirmed a significant influence on the experimental class using the 'Ali Level 3 Tajwid Thematic method, as demonstrated by an increase in average pretest and post-test scores. There was an average increase of 25.64 in tahsin score and 27.59 in tahfidz score after implementing the 'Ali Level 3 Thematic Tajwid Method. Furthermore, the Likert scale calculations showed that the implementation of the 'Ali Method worked very well for the female students at Rumah Tahfidz Fatimah, Daarul Iman Foundation, Bengkulu City.Keywords: 'Ali Method, Tahsin Al-Qur'an, Tahfidz Al-Qur'an